Understanding, interpretation and expression of spirituality and its influence on care and wellbeing : an explorative case study of a South African indigenous community - Ohajunwa, Chioma Ogochukwu (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.